(untitled) (Journal of Bangladesh Academy of Sciences, 2018)
To design a Reactor Pressure Vessel (RPV), material property like crack must be considered as it is an unavoidable property of materials. Presence of crack in materials must be kept within limit to prevent material’s failure. So, crack propagation must be analyzed and observed. In this paper, crack propagation due to stress and materials fracture toughness of reactor pressure vessel cladding has been observed to estimate cumulative probability of crack failure using Probabilistic Fracture Mechanics (PFM). Average crack size is guessed as 3 mm and geometry factor is considered as 1.12 to analyze edge crack. Final crack analysis range has been found to be 1.8 mm with crack propagation rate of ± 30% of its average size. Variation of critical crack size and crack initiation point for several design stresses and fracture toughness has been investigated with probabilistic fracture mechanics technique. The observed crack propagation by calculating final crack size and the cumulative crack failure probability of the reactor pressure vessel materials are presented in this work. Journal of Bangladesh Academy of Sciences, Vol. 41, No. 2, 237-245, 2017